Comparison of immunogenicity between hepatitis B vaccines with different dosages and schedules among healthy young adults in China: A 2-year follow-up study - Zhen-Zi Wang; Yu-Hua Gao; Ping Wang; Lin Wei; Chang-Ping Xie; Zhen-Xing Yang; Jian Lan; Zhong-Liao Fang; Ying Zeng; Ling Yan; Xue-En Liu; Hui Zhuang (Human Vaccines & Immunotherapeutics, 2018)
Immunogenicity of hepatitis B vaccine between 20 μg with 3-dose schedule and 60 μg with 2-dose regimens was compared 2 years after primary immunization. A total of 353 healthy adults aged 18–25 years were enrolled in the study and randomly assigned (1: 1: 1) into 3 vaccine groups: A (20 μg, 0–1–6 month), B (60 μg, 0–1 month) and C (60 μg, 0–2 month). Serum samples were collected at 1 month after a series vaccination and 12 months, 24 months after the first-dose. The GMC level of anti-HBs antibody was measured using Chemiluminescent Microparticle ImmunoAssay (CMIA). There were 59, 45 and 55 vaccinees available to follow-up with 2 year later in vaccine groups A, B and C, respectively. No significant differences existed in sex ratio, age and body mass index (BMI) among vaccinees at month 24 and the corresponding participants at baseline in each group (P > 0.05). The seroprotection rates in group A, B and C were 98.31%, 88.37% and 85.19%, respectively (P = 0.014), reflecting the fact that the rate of group A was significantly higher than that in group C (P = 0.026). Also, the GMC level of anti-HBs antibody in group A was significantly higher than those of other two groups (427.46 mIU/ml vs. 89.74 mIU/ml, 89.80 mIU/ml, respectively; all P < 0.01). This data suggested that the standard 20 μg (0–1–6 month) regimen of hepatitis B vaccine should be recommended as a priority on the premise of complete compliance in adults.